The Effect of Health Education about COVID-19 Through Social Media on COVID-19 Prevention Behavior - Alfiery Leda Kio; I Dewa Agung Gde Fanji Pradiptha (Universitas Aisyah Pringsewu, 2023)
The Coronavirus Disease 2019 (COVID-19) has now spread and it is recorded that 213 countries have contracted COVID-19 with thousands of new cases appearing every day. COVID-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which is a coronavirus that has never been previously identified in humans. The research objective was to identify the effect of health education about COVID-19 through social media on COVID-19 prevention behavior. The research hypothesis is that health education about COVID-19 through social media affects changing COVID-19 prevention behavior among students of Health Sciences College of Bina Usada Bali. This research used a pre-experimental method with one group pretest-posttest design. The research population was all nursing students in the second semester of Health Sciences College of Bina Usada Bali, with as many as 89 students. In taking the sampling used the total sampling technique. The data analysis technique used was the Wilcoxon test. The results after being given health education about COVID-19 showed that there was an effect of COVID-19 prevention behavior with a p-value of 0.001. Given the importance of public knowledge regarding COVID-19 prevention behavior so that the role of social media can be used as an educational medium to changing COVID-19 prevention behavior so that people avoid COVID-19. Abstrak: Coronavirus Disease 2019 2019 (COVID-19) saat ini telah menyebar dan tercatat 213 negara telah tertular COVID-19 dengan ribuan kasus baru yang muncul setiap harinya. COVID-19 merupakan penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) yang merupakan coronavirus yang belum pernah diidentifikasi sebelumnya pada manusia. Tujuan penelitian ini adalah untuk mengidentifikasi pengaruh edukasi kesehatan tentang COVID-19 melalui media sosial terhadap perilaku pencegahan COVID-19. Hipotesis penelitian yaitu edukasi kesehatan tentang COVID-19 melalui media sosial berpengaruh mengubah perilaku pencegahan COVID-19 di Kalangan Mahasiswa STIKES Bina Usada Bali. Penelitian ini menggunakan metode pre experimental dengan one group pretest – posttest design. Populasi penelitian adalah seluruh mahasiswa keperawatan semester II STIKES Bina Usada Bali yaitu sebanyak 89 Mahasiswa. Pengambilan sampel menggunakan teknik total sampling. Teknik analisa data yang digunakan adalah uji Wilcoxon. Hasil setelah diberikan Edukasi kesehatan tentang COVID-19 menunjukan ada pengaruh perilaku pencegahan COVID–19 dengan nilai p-value 0,001. Mengingat pentingnya pengetahuan masyarakat terkait perilaku pencegahan COVID-19 sehingga peran media sosial dapat dimanfaatkan sebagai salah satu media edukasi dalam mengubah perilaku pencegahan COVID-19 sehingga masyarakat terhindar dari COVID-19.